A comparative study of fluid-particle coupling methods for fully resolved lattice Boltzmann simulations. (1st September 2017) - Rettinger, C.; Rüde, U.
Highlights: Different fluid-particle coupling methods for LBM simulations are discussed. 3D benchmark of moving sphere with high particle Reynolds numbers is applied. Systematic comparison of coupling methods reveals their distinct characteristics. Particles must be resolved with at least 24 cells across for accurate results. Abstract: The direct numerical simulation of particulate systems offers a unique approach to study the dynamics of fluid-solid suspensions by fully resolving the submerged particles and without introducing empirical models. For the lattice Boltzmann method, different variants exist to incorporate the fluid-particle interaction into the simulation. This paper provides a detailed and systematic comparison of two different methods, namely the momentum exchange method and the partially saturated cells method by Noble and Torczynski. We discuss their algorithmic parts in detail, show and propose improvements to the commonly applied algorithms, and eventually identify three suitable subvariants of each method. These subvariants are used in the benchmark scenario of a single heavy sphere settling in ambient fluid to study their respective strengths and weaknesses in accurately reproducing characteristic physical phenomena for particle Reynolds numbers from 185 up to 365. The sphere must be resolved with at least 24 computational cells per diameter to achieve velocity errors below 5%. The momentum exchange method is found to be more accurate in predicting the streamwise velocity component whereas the partially saturated cells method is more accurate in the spanwise components. The study reveals that the resolution should be chosen with respect to the coupling dynamics, and not only based on the flow properties, to avoid large errors in the fluid-particle interaction.